An experimental study on gas–liquid two-phase countercurrent flow limitations of vertical pipes - Ma, Youfu; Zeng, Shanshan; Shao, Jie; Zhou, Tuo; Lyu, Junfu; Li, Jingfen; Lu, Peng (Experimental thermal and fluid science, 2023)
•The countercurrent flow limitation (CCFL) of vertical pipes was experimentally studied.•The effects of pipe diameter and pipe length on the CCFL were determined by experiment.•The existing CCFL correlation models were examined based on the experimental result.•A novel dimensionless group (Kuk0.5μk*0.1) was proposed for correlating diameter effect.•A new correlation predicting the diameter and length effects accurately was advanced. The gas–liquid two-phase countercurrent flow limitation (CCFL) of vertical pipes is an important subject of concern in various industries. Predicting the CCFL of vertical pipes, i.e. the flow rate relationship between the gas and liquid phases under CCFL conditions, has not yet been clearly determined on effects of the structural parameters of the pipe. In this study, a visualization experiment on the CCFL of vertical pipes was performed by using air and water as the two phases. The effects of pipe diameter and pipe length were tested in the ranges of 25–100 mm and 0.50–2.0 m, respectively. Based on the experimental result, the flow behaviors of the CCFL in vertical pipes were analyzed, and four existing CCFL correlation models were examined in their capabilities to correlate the effects of pipe diameter and pipe length. The result shows that the flow patterns in vertical pipes are essentially annular flows and annular-mist flows under CCFL conditions, and the flow behaviors on gas–liquid interface present different features as the pipe differed in diameters. Examination of the available CCFL models indicates that none of them has reached a satisfactory correlation on the effects of pipe diameter and pipe length. Consequently, based on a reasonable fluid mechanics analysis, a novel CCFL correlation model that can correlate the effects of pipe diameter and pipe length was advanced. This model provides a reasonable and accurate prediction of the CCFL of vertical pipes when the pipe varies in structural parameters, which is of great significance to the safe and efficient operation of the related equipment in nuclear power generation, natural gas extraction and chemical industries.